How financial and non–financial rewards moderate the relationships between transformational leadership, job satisfaction, and job performance - Hsinkuang Chi; Thinh–Van Vu; Hoang Viet Nguyen; Thanh Ha Truong (Cogent Business & Management, 2023)
While extensive literature is available on the relationships between transformational leadership, job satisfaction, rewards, and job performance, few studies examine the moderating roles of financial and non-financial rewards on these relationships. This study examines the moderating effects of financial and non-financial rewards on transformational leadership-job performance and job satisfaction-job performance relationships. It also examines the mediating effect of job satisfaction on transformational leadership and job performance. The data were obtained through questionnaires that were distributed to employees (N = 331) of private enterprises in Vietnam. The study uses the SPSS 23.0 software and the PROCESS V3.4 to test the hypotheses. The results demonstrate that transformational leadership significantly affects job satisfaction, which, in turn, is strongly associated with job performance. Job satisfaction also has a mediating effect on the relationship between transformational leadership and job performance. Interestingly, neither financial nor non-financial rewards have any moderating effect on the relationship between job satisfaction and job performance, but financial rewards have a negative moderating effect on the relationship between transformational leadership and job performance. These findings suggest that managers may benefit from combining transformational leadership with financial rewards to motivate employees and improve job performance.
Keywords: 650; job satisfaction; job performance; transformational leadership; financial reward; non-financial reward